System Approach in Road Safety Studies - Andrzej Szymanek (Communications - Scientific letters of the University of Zilina, 2020)
The road safety management methodology should be based on a system approach. This means that the road transport must be formalized as a complex system (CS), and then safety can be interpreted as an emergent feature of such a system. Road accidents should be interpreted as "organizational accidents". They should be studied using concepts such as "normal accident theory" (NAT) and "highly reliable organization" (HRO). The main purpose of the article is to show the usefulness of these concepts for the road safety and risk management, especially in Polish conditions. The system approach to road safety research (and transport safety) will allow for the better safety results.